Comparison of Drug and Cell‐Based Delivery: Engineered Adult Mesenchymal Stem Cells Expressing Soluble Tumor Necrosis Factor Receptor II Prevent Arthritis in Mouse and Rat Animal Models. (16th April 2013) - Liu, Linda N.; Wang, Gang; Hendricks, Kyle; Lee, Keunmyoung; Bohnlein, Ernst; Junker, Uwe; Mosca, Joseph D.
Abstract : Human soluble tumor necrosis factor receptor II (hsTNFR) protein delivery from genetically engineered human mesenchymal stem cells (hMSCs) was compared with that of etanercept. Implanted hsTNFR‐transduced mesenchymal stem cells reduced mouse serum circulating tumor necrosis factor‐α (TNFα) generated from either implanted TNFα‐expressing cells or lipopolysaccharide induction more effectively than etanercept, suggesting faster clearance of the soluble tumor necrosis factor receptor‐TNFα complex from the animals. The data support the utility of hMSCs as therapeutic gene delivery vehicles and their potential to be used in alleviating inflammation within the arthritic joint. Abstract : Rheumatoid arthritis (RA) is a systemic autoimmune disease with unknown etiology where tumor necrosis factor‐α (TNFα) plays a critical role. Etanercept, a recombinant fusion protein of human soluble tumor necrosis factor receptor II (hsTNFR) linked to the Fc portion of human IgG1, is used to treat RA based on the rationale that sTNFR binds TNFα and blocks TNFα‐mediated inflammation. We compared hsTNFR protein delivery from genetically engineered human mesenchymal stem cells (hMSCs) with etanercept. Blocking TNFα‐dependent intercellular adhesion molecule‐1 expression on transduced hMSCs and inhibition of nitric oxide production from TNFα‐treated bovine chondrocytes by conditioned culture media from transduced hMSCs demonstrated the functionality of the hsTNFR construction. Implanted hsTNFR‐transduced mesenchymal stem cells (MSCs) reduced mouse serum circulating TNFα generated from either implanted TNFα‐expressing cells or lipopolysaccharide induction more effectively than etanercept (TNFα, 100%; interleukin [IL]‐1α, 90%; and IL‐6, 60% within 6 hours), suggesting faster clearance of the soluble tumor necrosis factor receptor (sTNFR)‐TNFα complex from the animals. In vivo efficacy of sTNFR‐transduced MSCs was illustrated in two (immune‐deficient and immune‐competent) arthritic rodent models. In the antibody‐induced arthritis BalbC/SCID mouse model, intramuscular injection of hsTNFR‐transduced hMSCs reduced joint inflammation by 90% compared with untransduced hMSCs; in the collagen‐induced arthritis Fischer rat model, both sTNFR‐transduced rat MSCs and etanercept inhibited joint inflammation by 30%. In vitro chondrogenesis assays showed the ability of TNFα and IL1α, but not interferon γ, to inhibit hMSC differentiation to chondrocytes, illustrating an additional negative role for inflammatory cytokines in joint repair. The data support the utility of hMSCs as therapeutic gene delivery vehicles and their potential to be used in alleviating inflammation within the arthritic joint.